Insulin regulates Nedd4-2 via a PKB-dependent mechanism in HEI-OC1 auditory cells-crosstalks with sphingolipid and cAMP signaling. (2nd January 2022) - Pålbrink, Ann-Ki; Morén, Björn; Stenkula, Karin G.; Magnusson, Måns; Degerman, Eva
Abstract: Background: The mechanisms of association between diabetes and inner ear dysfunction are unknown, although endolymphatic hydrops may be involved. We have previously shown that insulin signaling components are expressed in human saccule and that insulin signaling takes place in HEI-OC1 auditory cells. Aim: To explore Nedd4-2 as a target for insulin signaling. Materials and methods: Effects of insulin were analyzed using western blot and confocal microscopy in HEI-OC1 auditory cells. Results: Insulin induced phosphorylation of Nedd4-2 and increased the amount of ENaC at the plasma membrane. Also, protein kinase B (PKB) and NDRG1, a substrate for SGK1 (serum and glucocorticoid stimulated kinase), were phosphorylated in response to insulin. The SGK1 inhibitor GSK650394 prevented insulin-induced phosphorylation of NRDG1, but not of PKB and Nedd4-2, whereas the phosphatidylinositol 3-kinase (PI3K) inhibitor wortmannin and the PKB inhibitor MK2206 inhibited phosphorylation of all components. Ceramides prevented insulin-induced phosphorylation of PKB and NDRG1, but not of Nedd4-2. The ceramide metabolite sphingosine 1-phosphate induced phosphorylation of Nedd4-2. Conclusions: Insulin induces phosphorylation of Nedd4-2, most likely involving PI3K/PKB signaling. Sphingosine 1-phosphate might protect Nedd4-2 against ceramide-induced insulin resistance. Significance: Insulin-mediated regulation of Nedd4-2 might impact on inner ear sodium homeostasis with implications for diabetes-induced inner ear damage.